MoHE Minister celebrates UMPSA students during Ramadan Semarak Programme - Naqiah, Puaad (UMPSA, 2024)
GAMBANG, 4 April 2024 - Minister of Higher Education, Yang Berhormat Dato’ Seri Diraja Dr. Zambry Abd Kadir continued his tour of the MoHE’s Semarak Ramadan programme by visiting Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) recently.